Desenvolvimento, caracterização e avaliação in vitro e in vivo de complexos contendo hidroclorotiazida, β-ciclodextrina e colato de sódio - Severino Júnior, Pedro Nicolau (2016)
Hydrochlorothiazide (HCTZ) is a drug that belongs to the class of thiazide diuretics. It is a heterocyclic compound having the formula C7H8ClN3O4S2, being formed by two sulfonamide groups. Known for more than half century, it is one of the drugs of choice when treating high blood pressure and its mechanism of action is based on increased renal sodium excretion. According to the Biopharmaceutical Classification System (BCS), Hydrochlorothiazide belongs to the IV class, ie very low solubility and perme- ability, and its bioavailability around 65%. The aim of this study was to improve these aspects of Hydrochlorothiazide by complexation with the cyclic oligomer β- cyclodextrin (βCD) and the bile salt hydrated sodium cholate (HCOL). Also a new HPLC method was developed and validated for the identification of HCTZ and its degradation products 4-amino-6-chloro disulfonamide (DSA) and chlorothiazide (CTZ). The method proved to be specific, linear, accurate, precise and robust. In the in-vitro dissolution test (simulated gastric fluid, pH 1.2) the release profile of the HCTZ was improved for the formulation containing HCTZ: βCD: COL. On the photo- stability assays it was verified that the complexation improved the stability of the drug against light. The in-vivo assays showed an increase on the urinary volume and the eletrolytes excretion on the groups that was administrated the inclusion complex con- taining sodium cholate. According to the data presented, the complexes containing cholate achieved the best dissolution results, which may indicate a greater amount of drug in the intestinal lumen and consequent improvement of its therapeutic effect. It can be concluded that the complexation of hydrochlorothiazide represents an im- provement of its therapeutic effect.